College of arts and science the Joseph A. Sellinger, S.J. school of business and managemet (Maryland, 1995)
This book introduce about the college, academic regulations and policies, financial information, financial aid. Introduce college of arts and science, the Joseph A. Sellinger, S.J. school of business and management.
Keywords: Đại học và cao đẳng,Universities and colleges; Việc tốt nghiệp,Graduate work